Proceedings of the International Conference on Business, Economic, Social Science and Humanities (ICOBEST 2018) 2018
DOI: 10.2991/icobest-18.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Entrepreneurial Motivation on Entrepreneurship Intention

Abstract: This research aimed at determining the impact of entrepreneurial motivation on entrepreneurship intention. Method used in this research was quantitative analysis using path analysis with validity and reliability test. Sampling method used in this research is random sampling through the distribution of a series of questionnaires to 172 students at a private university as a case study. This research investigated perceived behavioral control and subjective norm as dimensions in an entrepreneurial motivation varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(12 reference statements)
1
3
0
3
Order By: Relevance
“…Entrepreneurship studies have become a more prominent discipline than mainstream education, and a recent study has shown that EMs play a crucial role in EI (Iffan, 2018). Our analysis shows ( p = *** ) that EM mediates the relationship (H8) of EE and EI which is supported by earlier observations (Iffan, 2018; Kim-Soon et al. , 2020) (see Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship studies have become a more prominent discipline than mainstream education, and a recent study has shown that EMs play a crucial role in EI (Iffan, 2018). Our analysis shows ( p = *** ) that EM mediates the relationship (H8) of EE and EI which is supported by earlier observations (Iffan, 2018; Kim-Soon et al. , 2020) (see Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…Employee creativity and motivation have been universal concepts that warrant extensive research (Hon and Leung, 2011) and EM is countryspecific (Carsrud and Br€ annback, 2011;Hessels et al, 2008). Recent investigations suggest that creativity and motivation are strongly associated with student outcomes (Iffan, 2018;Kim-Soon et al, 2014;Liao et al, 2018). The following hypotheses are proposed in this work with the above extensive literature arguments.…”
Section: The Mediating Role Of Creativity and Motivationmentioning
confidence: 88%
“…Entrepreneurial commitment was assessed with a measurement scale based on Iffan (2018) , with 10 items, comprising affection commitment (items 1–4), behavior commitment (items 5–9), and continuance commitment (items 9–10).…”
Section: Methodsmentioning
confidence: 99%
“…Hasil penelitian ini menunjukkan bahwa efikasi diri berpengaruh positif dan signifikan terhadap niat berwirausaha. Kemudian, Iffan (2018) menunjukkan bahwa motivasi wirausaha berpengaruh signifikan terhadap peningkatan niat berwirausaha. Semakin tinggi motivasi wirausaha, maka semakin besar keberanian untuk mengambil tindakan meluncurkan bisnis baru berdasarkan niat berwirausaha.…”
Section: Pendahuluan Latar Belakangunclassified
“…menunjukkan bahwa masyarakat yang penasaran atau ingin tahu tentang kewirausahaan didorong oleh motivasi yang ada untuk mengubah niat tersebut menjadi usaha baru Iffan (2018). menunjukkan bahwa motivasi wirausaha mempunyai pengaruh yang signifikan terhadap peningkatan niat berwirausaha.…”
unclassified